Temperature and Inoculum Origin Influence the Performance of Ex-Situ Biological Hydrogen Methanation - Noémie Figeac; Eric Trably; Nicolas Bernet; Jean-Philippe Delgenès; Renaud Escudié (Molecules, 2020)
The conversion of H2 into methane can be carried out by microorganisms in a process so-called biomethanation. In ex-situ biomethanation H2 and CO2 gas are exogenous to the system. One of the main limitations of the biomethanation process is the low gas-liquid transfer rate and solubility of H2 which are strongly influenced by the temperature. Hydrogenotrophic methanogens that are responsible for the biomethanation reaction are also very sensitive to temperature variations. The aim of this work was to evaluate the impact of temperature on batch biomethanation process in mixed culture. The performances of mesophilic and thermophilic inocula were assessed at 4 temperatures (24, 35, 55 and 65 °C). A negative impact of the low temperature (24 °C) was observed on microbial kinetics. Although methane production rate was higher at 55 and 65 °C (respectively 290 ± 55 and 309 ± 109 mL CH4/L.day for the mesophilic inoculum) than at 24 and 35 °C (respectively 156 ± 41 and 253 ± 51 mL CH4/L.day), the instability of the system substantially increased, likely because of a strong dominance of only Methanothermobacter species. Considering the maximal methane production rates and their stability all along the experiments, an optimal temperature range of 35 °C or 55 °C is recommended to operate ex-situ biomethanation process.